2023
DOI: 10.1097/md.0000000000032741
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of an angiogenesis-related signature associated with preeclampsia by bioinformatic analysis

Abstract: Preeclampsia (PE) is a pregnancy disorder with high morbidity and mortality rates for both mothers and newborns. This study explores potential diagnostic indicators of PE. We downloaded the messenger ribonucleic acid profiles of the GSE75010 dataset from the Gene Expression Omnibus database, and used placenta samples to carry out different analyses including differential expression, Gene Ontology, and Kyoto Encyclopedia of Genes and Genomes analyses. Least absolute shrinkage and selection operator r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…A study reported the establishment of a 12-gene risk signature, which demonstrated high accuracy in predicting PE during pregnancy (AUC = 0.90). [35] Wang et al suggested that LEP overexpression is associated with PE and may be a potential diagnostic marker and therapeutic target. Immune cell infiltration analysis showed that M1 and M2 macrophages differed between normal pregnancies and those in PE patients.…”
Section: Discussionmentioning
confidence: 99%
“…A study reported the establishment of a 12-gene risk signature, which demonstrated high accuracy in predicting PE during pregnancy (AUC = 0.90). [35] Wang et al suggested that LEP overexpression is associated with PE and may be a potential diagnostic marker and therapeutic target. Immune cell infiltration analysis showed that M1 and M2 macrophages differed between normal pregnancies and those in PE patients.…”
Section: Discussionmentioning
confidence: 99%
“…Taking all these factors into consideration, we might suspect that chemerin in PE should have an anti-angiogenic rather than a pro-angiogenic effect; however, to date, there is no evidence for that; thus, this issue needs further investigation. Interestingly, in a recently published study, Ma et al performed a bioinformatic analysis of angiogenesis-related genes and identified including 12 upregulated genes and 17 downregulated genes that are associated with PE; however, they were not related to chemerin and other adipokines, suggesting that the role of chemerin in PE development might be related to biological effects other than the regulation of angiogenesis [ 107 ].…”
Section: Potential Role Of Chemerin In the Pathophysiology Of Pementioning
confidence: 99%